A novel method for removing organic sulfur from high-sulfur coal: Migration of organic sulfur during microwave treatment with NaOH-H2O2. (1st April 2021) - Cai, Shuangshuang; Zhang, Shengfu; Wei, Yuyang; Sher, Farooq; Wen, Liangying; Xu, Jian; Dang, Jie; Hu, Liwen
Graphical abstract: Highlights: Organic sulfur was removed from coal by microwave combined with NaOH-H2 O2 . Organic sulfur is mainly transformed into liquid sulfur. The S=O functional group is the hardest to remove. Density functional theory was used to support the experimental results. Abstract: A novel technology of removing organic sulfur from coal was proposed by microwave irradiation combined with NaOH-H2 O2 . The organic sulfur removal degree and the transformation of sulfur-containing compounds in coal was also analyzed using Inductively coupled plasma (ICP) and Fourier transform infrared (FTIR) during desulfurization. The changes of bond order, bond length, Fukui indices and electrostatic potential charge of sulfur-containing bond were further calculated to support the experimental results. The results show that organic sulfur is mainly transformed into SO3 2− and SO4 2− under solvent-assisted microwave irradiation. For three typical organic sulfur functional groups, the disulfide bond (S–S) is the easiest to remove, while the sulfuryl (S=O) is the hardest to remove, which could be explained by the strength of the sulfur-containing bond and the reactivity of S atoms in different functional groups. The order of bond lengths of the sulfur-containing bond is S–S > –SH > S=O. Furthermore, the reactivity of S atoms is much higher than that of C atoms in coal matrix, indicating that this method can be used as an effective process on the removal of organic sulfur without destruction of coal matrix.